2008
DOI: 10.1016/j.engfracmech.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of plasticity induced crack closure: Identification and discussion of parameters

Abstract: Numerical studies play a major role in the understanding and prediction of plasticity induced crack closure (PICC). However, the available numerical models can be considered simplifications of reality as they consider discrete crack propagations, relatively high fatigue crack growth rates (FCGR), sharp cracks, and propagation occurring at well-defined loads. Besides, there are a great number of numerical and physical parameters affecting the predictions of PICC. The aim of this paper is to discuss the numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…For a review pertaining to modeling aspects on the subject, see Solanki et al [35], and more recent work can be found for example in Refs. [36,37]. In our model, the normal, frictionless contact formulation in ABAQUS [38] was employed.…”
Section: Model Descriptionmentioning
confidence: 99%
“…For a review pertaining to modeling aspects on the subject, see Solanki et al [35], and more recent work can be found for example in Refs. [36,37]. In our model, the normal, frictionless contact formulation in ABAQUS [38] was employed.…”
Section: Model Descriptionmentioning
confidence: 99%
“…To avoid the locking effect, a selective reduced integration method is used in DD3IMP [44,45]. The optimum values of the numerical parameters of the DD3IMP implicit algorithm have been well established in previous works, concerning the numerical simulation of sheet metal forming processes [46] and PICC [47].…”
Section: Numerical Modelmentioning
confidence: 99%
“…To avoid the locking effect a selective reduced integration method is used in DD3IMP [87]. The optimum values of the numerical parameters of the DD3IMP implicit algorithm have been well established in previous works, concerning the numerical simulation of sheet metal forming processes [88] and PICC [89].…”
Section: Numerical Modelmentioning
confidence: 99%